2014
DOI: 10.1177/0003319714527638
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil–Lymphocyte Ratio and Carotid–Intima Media Thickness in Patients With Behçet Disease Without Cardiovascular Involvement

Abstract: Behçet disease (BD) is associated with endothelial dysfunction and chronic inflammation. The neutrophil-lymphocyte (N/L) ratio and carotid intima-media thickness (cIMT) are markers of inflammation and vascular risk, respectively. We assessed the relationship between cIMT values and N/L ratio in BD (65 patients and 62 control participants). There were statistically significant differences in N/L ratios and cIMT values between the patients with BD and control group (P < .001). There were moderate positive correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
86
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 33 publications
10
86
3
2
Order By: Relevance
“…In context, the NLR may use activity marker for BD patients. We have shown that NLR levels were significantly higher in active BD patients compared with inactive patients [6].…”
mentioning
confidence: 76%
“…In context, the NLR may use activity marker for BD patients. We have shown that NLR levels were significantly higher in active BD patients compared with inactive patients [6].…”
mentioning
confidence: 76%
“…Recently, NLR has begun to be used to measure severity of inflammation in a variety of diseases like cardiovascular diseases, malignancies and dia- betes. [22] In a study by Demir et al, [23] NLR was related to inflammation linked to myocardial ischemia while another study by Muhammed Suliman et al [24] stated that NLR was an inexpensive method to show inflammation in acute coronary diseases. In our study, we did not find a significant difference between patient and control groups in terms of NLR values.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence supports a role for neutrophil/lymphocyte ratio (NLR) as a cheap and simple disease activity marker in BD. NLR has been proposed as a surrogate marker for endothelial dysfunction and inflammation, and several authors have proposed the use of NLR as part of evaluation for disease activity in BD [184][185][186][187].…”
Section: Neutrophil Hyperfunction and Endothelial Cell Activationmentioning
confidence: 99%